Germany's New Right as Culture and Politics - Woods, R. (New Perspectives in German Political Studies, 2007)
This is the first full-length study in English of the New Right in Germany and it breaks new ground by considering the New Right as a political and a cultural movement. The book examines the often contradictory motives that feed into New Right political pronouncements and explores the cultural thinking that feeds into extreme political commitment.